Toward an integrated approach to positive development: Implications for intervention. Issue 3 (2nd July 2016) - Tolan, Patrick; Ross, Katherine; Arkin, Nora; Godine, Nikki; Clark, Erin
ABSTRACT: Positive development models shift focus for intervention from avoiding problems, deficits, or psychopathology to promoting skills, assets, and psychological well-being as the critical interests in development and intervention. The field can be characterized as multiple parallel lines of empirical inquiry from four frameworks: Social Competence, Social and Emotional Learning, Positive Youth Development, and Positive Psychology. This review is meant to organize understanding of implications for intervention by comparing these four frameworks along several dimensions including (1) key conceptual frameworks and constructs, (2) populations of interest, (3) measurement practices, and (4) intervention design and content implications to point out areas of overlap and distinction. Furthermore, the authors provide suggestions for the advancement beyond isolated scientific inquiry and unclear overlap and distinction, toward a more integrated approach to study and intervention design that promotes positive development.